Identifying The Common Type of Spelling Error by Leveraging Levenshtein Distance and N-gram - Hardiyanti, Margareta (Scientific Journal of Informatics, 2021)
Purpose: This study aims to identify the common type of spelling error and it uses the list of common misspelling words submitted by Wikipedia contributors. Methods: Levenshtein and N-gram distance are utilized to predict the correct word of misspelling from English dictionary. Then, the result of both algorithms is observed and evaluated using recall metrics to determine which technique works more effectively. Result: The result of this study shows that Levenshtein works well to correct substitution single letter and transposition two sequenced letters, while N-gram operates effectively to fix the word with letter omission. The overall result is then evaluated by recall measurement to see which technique that works well on correcting the misspellings. Since the recall of Levenshtein is higher than N-gram, it is concluded that the frequency of misspelling words that are correctly fixed by Levenshtein occurs more often. Novelty: This is the first study that compares two spelling correction algorithms on identifying the common type of spelling error.